Peningkatan Hasil Belajar PAI Menggunakan Model Make A Match Kelas IV SDN 01 Langsat Kadap - Maisaroh, Maisaroh (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to improve student learning outcomes in Islamic Religious Education using the Make a Match learning model. The research was conducted in two cycles, namely cycle I and cycle II, involving 15 students of grade IV at SDN 01 Langsat Kadap. The results showed a significant improvement in student learning activity, teacher teaching activity, and student problem-solving ability scores. In cycle I, student learning activity reached 70%, while in cycle II it increased to 86%. Similarly, the teacher's teaching activity increased from 42.5% in cycle I to 87.5% in cycle II. The student learning outcomes in the final test of cycle II showed a significant improvement, from 65% in cycle I to 90% in cycle II, which is categorized as very high. Based on these results, it can be concluded that the Make a Match learning model effectively improves student learning activity and learning outcomes in Islamic Religious Education.